2015
DOI: 10.1007/s00198-015-3226-7
|View full text |Cite
|
Sign up to set email alerts
|

Myostatin deficiency partially rescues the bone phenotype of osteogenesis imperfecta model mice

Abstract: Myostatin deficiency partially improved the reduced femoral bone biomechanical strength of adult +/oim mice by increasing muscle mass with concomitant improvements in bone microarchitecture and physiochemical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 48 publications
0
21
1
Order By: Relevance
“…We do not know whether the observed increases in BMC and BMD represent a direct effect of the ActRIIB.Fc on the bone or an indirect effect resulting from increased muscle mass. Positive correlation between muscle mass and bone mass has been reported with partial or complete myostatin inactivation in mice [50,51,53,54]. Recent studies suggest that myostatin may have direct catabolic effects on bone metabolism [5558].…”
Section: Discussionmentioning
confidence: 99%
“…We do not know whether the observed increases in BMC and BMD represent a direct effect of the ActRIIB.Fc on the bone or an indirect effect resulting from increased muscle mass. Positive correlation between muscle mass and bone mass has been reported with partial or complete myostatin inactivation in mice [50,51,53,54]. Recent studies suggest that myostatin may have direct catabolic effects on bone metabolism [5558].…”
Section: Discussionmentioning
confidence: 99%
“…Hamrick revealed that GDF8 deficiency had load‐dependent effects on the increased osteogenic differentiation of bone marrow‐derived mesenchymal stem cells (BMSCs) in mice . Another study confirmed that the lack of GDF8 improved the reduced femoral bone biomechanical strength of osteogenesis imperfecta model mice partially . In addition, GDF8 regulates osteoclast differentiation directly and its inhibition reduced bone erosion in arthritis model mice .…”
Section: Introductionmentioning
confidence: 94%
“…9 Another study confirmed that the lack of GDF8 improved the reduced femoral bone biomechanical strength of osteogenesis imperfecta model mice partially. 10 In addition, GDF8 regulates osteoclast differentiation directly and its inhibition reduced bone erosion in arthritis model mice. 11 However, the functions of GDF8 in bone formation and bone resorption require further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Myostatin may play a more prominent role in the pathogenesis of disease states that affect bone. Using a mouse model of osteogenesis imperfecta, genetically reduced levels of myostatin improved muscle mass and bone strength . In a mouse model of rheumatoid arthritis, myostatin gene knockout or administration of an inhibitory antibody against myostatin reduced bone erosion .…”
Section: Myostatinmentioning
confidence: 99%
“…Using a mouse model of osteogenesis imperfecta, genetically reduced levels of myostatin improved muscle mass and bone strength . In a mouse model of rheumatoid arthritis, myostatin gene knockout or administration of an inhibitory antibody against myostatin reduced bone erosion . Mice administered RAP‐031, a soluble form of the activin IIB receptor that binds and inactivates myostatin and other activin IIB receptor ligands, had larger pectoralis, rectus femoris, and gastrocnemius muscles, and these alterations were associated with increased trabecular number and bone volume fraction (BV/TV) at the proximal tibia .…”
Section: Myostatinmentioning
confidence: 99%